Nefropatía por poliomavirus en un paciente inmunosuprimido por trasplante renal secundario a la enfermedad de arteritis de Takayasu - Godoy Carrillo, María Claudia (2016)
Polyomavirus nephropathy is a disease that predominates in renal transplant patients due to the immunosuppressive treatment for the maintenance of the renal graft. The current prevalence of this disease ranges between 1-14%. The suspicion of the disease comes from the presence of decoy cells in urine samples and the gold standard for the diagnosis is the presence of viral inclusions in the renal biopsy. In this case report, we describe a patient with a renal transplant secondary to Takayasu arteritis who presented renal failure evidenced by progressive elevation of serum creatinine. The renal biopsy showed viral inclusions, confirming the diagnosis.